Effects of a prior authorization policy for extended‐release/long‐acting opioids on utilization and outcomes in a state Medicaid program. (4th June 2018) - Keast, Shellie L.; Kim, Hyunjee; Deyo, Richard A.; Middleton, Luke; McConnell, K. John; Zhang, Kun; Ahmed, Sharia M.; Nesser, Nancy; Hartung, Daniel M.
Abstract: Background and aims: In response to the opioid overdose epidemic, US state Medicaid programs have adopted restrictive policies for opioid analgesics, yet effects on prescribing patterns and health outcomes are uncertain. This study aimed to examine effects of a prior authorization policy for extended‐release/long‐acting (ER/LA) opioids on opioid use in the Oklahoma, USA state Medicaid program. Design: Retrospective difference‐in‐differences design study comparing changes in opioid use in Oklahoma Medicaid to control (Oregon Medicaid). Setting: Oklahoma and Oregon, USA. Participants: Medicaid beneficiaries in the Oklahoma and Oregon fee‐for‐service Medicaid programs between July 2007 and June 2009 (33 724 in Oklahoma and 13 520 in Oregon) Measurements: The primary outcome was incident opioid‐naive ER/LA opioid use. Secondary outcomes included other opioid and non‐opioid pain medication use. We also examined indicators of high‐risk prescribing (e.g. high‐dosage opioid use) and opioid‐related hospitalizations or emergency department (ED) visits. Findings: The prior authorization policy was associated with a 0.7 percentage point reduction in the likelihood of incident opioid‐naive ER/LA opioid use [95% confidence interval (CI) = −1.16 to −0.33 percentage points; 70% pre‐policy mean reduction, a 1.4 percentage point decrease in likelihood of any new ER/LA opioid prescriptions (95% CI = –2.1 to −0.7 percentage points; 33% pre‐policy mean reduction) and a decline of 0.16 in total ER/LA opioid prescriptions per enrollee (PPE) (95% CI = –0.29 to −0.04 PPE)]. There was a significant increase in the number of short‐acting opioids filled after the policy (0.36; 95% CI = 0.22–0.50 PPE), increases in likelihood of having overlapping opioids and benzodiazepines, but significant reductions in likelihood of having overlapping opioids. No significant changes in opioid‐related hospitalizations or ED visits were observed. Conclusions: In Oklahoma, USA's July 2008 prior authorization policy for extended‐release/long‐acting opioids appears to have reduced the number of opioid‐naive patients initiating extended‐release/long‐acting opioid use by more than half, but may also have increased short‐acting opioid prescriptions by 7%.